2020
DOI: 10.3390/nu12082438
|View full text |Cite
|
Sign up to set email alerts
|

Do the Dietary Intakes of Pregnant Women Attending Public Hospital Antenatal Clinics Align with Australian Guide to Healthy Eating Recommendations?

Abstract: The maternal diet influences the long-term health status of both mother and offspring. The current study aimed to compare dietary intakes of pregnant women compared to food and nutrient recommendations in the Australian Guide to Healthy Eating (AGHE) and Nutrient Reference Values (NRVs). Usual dietary intake was assessed in a sample of women in their 3rd trimester of pregnancy attending antenatal outpatient clinics at John Hunter Hospital, Newcastle, New South Wales (NSW). Dietary intake was measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 40 publications
11
37
0
Order By: Relevance
“…The Australian Dietary Guidelines recommend 2 servings of fruit and 5 serves of vegetables (including legumes) each day during pregnancy [ 26 ]. Similar to previous studies, our dietary intake analysis demonstrated that pregnant women are not meeting nutritional guidelines [ 20 , 27 , 28 , 29 , 30 ]. In this study, the median fruit intake for the pregnant women was 1.6 serves per day, with only a quarter (24.8%) of the women meeting the target aim of two serves of fruit per day.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The Australian Dietary Guidelines recommend 2 servings of fruit and 5 serves of vegetables (including legumes) each day during pregnancy [ 26 ]. Similar to previous studies, our dietary intake analysis demonstrated that pregnant women are not meeting nutritional guidelines [ 20 , 27 , 28 , 29 , 30 ]. In this study, the median fruit intake for the pregnant women was 1.6 serves per day, with only a quarter (24.8%) of the women meeting the target aim of two serves of fruit per day.…”
Section: Discussionsupporting
confidence: 87%
“…Even more concerning was our finding that only 3.5% ( n = 28) of the pregnant women in this study met the Australian Dietary Guidelines recommendation for 5 serves of vegetables (including legumes) per day [ 25 ]. Our findings for fruit intake were comparable to those from previous Australian-based studies in which the dietary intake of pregnant women was assessed [ 20 , 27 , 28 , 29 ]. In a recent observational study by Slater et al (2020), using the Australian Eating Survey method to assess intakes of 503 pregnant women, the median fruit intake was 1.7 serves of fruit, with only 38.2% meeting the target of 2 serves per day [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Sodium intake above the recommended level has also been reported in a remote Indigenous Australian general population, where 46% of all sodium intake was contributed by discretionary salt, bread and processed meat [ 59 ]. Findings were similar in a number of studies conducted in the wider population of pregnant women from Australia [ 60 , 61 , 62 , 63 , 64 ], the United States of America [ 65 ] and the United Kingdom [ 66 ]. There are potential health consequences associated with a high-fat, high-sodium diet, particularly in highly processed foods during pregnancy, including altered placental function and predisposition to metabolic disease in the offspring [ 67 ].…”
Section: Discussionsupporting
confidence: 79%